Zip4 (Slc39a4) expression is activated in hepatocellular carcinomas and functions to repress apoptosis, enhance cell cycle and increase migration. - Benjamin P Weaver; Yuxia Zhang; Stephen Hiscox; Grace L Guo; Udayan Apte; Kathryn M Taylor; Christian T Sheline; Li Wang; Glen K Andrews (PLoS ONE)
Background The zinc transporter ZIP4 (Slc39a4) is important for proper mammalian development and is an essential gene in mice. Recent studies suggest that this gene may also play a role in pancreatic cancer. Methods/principal findings Herein, we present evidence that this essential zinc transporter is expressed in hepatocellular carcinomas. Zip4 mRNA and protein were dramatically elevated in hepatocytes in the majority of human hepatocellular carcinomas relative to noncancerous surrounding tissues, as well as in hepatocytes in hepatocellular carcinomas occurring in farnesoid X receptor-knockout mice. Interestingly, meta-analysis of microarray data in the Geo and Oncomine databases suggests that Zip4 mRNA may also be elevated in many types of cancer. Potential mechanisms of action of ZIP4 were examined in cultured cell lines. RNAi knockdown of Zip4 in mouse Hepa cells significantly increased apoptosis and modestly slowed progression from G(0)/G(1) to S phase when cells were released from hydroxyurea block into zinc-deficient medium. Cell migration assays revealed that RNAi knockdown of Zip4 in Hepa cells depressed in vitro migration whereas forced over-expression in Hepa cells and MCF-7 cells enhanced in vitro migration. Conclusions ZIP4 may play a role in the acquisition of zinc by hepatocellular carcinomas, and potentially many different cancerous cell-types, leading to repressed apoptosis, enhanced growth rate and enhanced invasive behavior.